Síntese e caracterização textural do catalisador CeO2/TiO2 obtido via sol-gel: fotocatálise do composto modelo hidrogenoftalato de potássio - Valente, J. P. S. [UNESP]; Araújo, A. B [UNESP]; Bozano, D. F; Padilha, P. M. [UNESP]; Florentino, A. O. [UNESP] (Editora Unesp, 2005)
Este trabalho descreve um método de modificação do TiO2 obtido pelo processo sol-gel, através da adição de óxido de cério no momento da síntese. O material foi caracterizado por adsorção de N2 a 77K. A adição de CeO2 aumenta a área específica do catalisador em 135% e reduz o diâmetro de poros. A atividade catalítica desses materiais foi verificada frente à reação de foto-decomposição do hidrogenoftalato de potássio e comparada ao TiO2 comercial P25 da Degussa.

This work describes the modification of the TiO2, obtained by sol-gel process, with the cerium oxide addition. The material was characterized by N2 adsorption at 77K. The addition of CeO2 increases the specific area in 135% and reduces the pores diameter of the catalyst. The catalytic activity was verified by reaction of decomposition of the potassium hidrogenphthalate. The results were compared to the TiO2 P25 (Degussa).
Synthesis and textural characterization of CeO2/TiO2 obtained by sol-gel process: photocatalysis of model compound potassium hidrogenphthalate
Keywords: fotocatálise; CeO2/TiO2; sol-gel; caracterização textural; atividade fotocatalítica; photocatalysis; CeO2/TiO2; sol-gel; textural characterization; photocatalytic activity